An unexpected friend − ROS in apoptosis-induced compensatory proliferation: Implications for regeneration and cancer. (August 2018) - Diwanji, Neha; Bergmann, Andreas
Abstract: Apoptosis-induced compensatory proliferation (AiP) is a form of compensatory proliferation that is triggered by apoptotic cell death to maintain tissue homeostasis. As such, AiP is essential for many tissue repair processes including regeneration. The apoptotic effectors, termed caspases, not only execute apoptosis, but are also directly involved in the generation of the signals required for AiP. Reactive oxygen species (ROS) play an important role for regenerative processes. Recently, it was shown in Drosophila that apoptotic caspases can mediate the generation of ROS for promoting AiP. This review summarizes and discusses these findings in the context of regenerative processes and cancer.